Combined perineal massage and warm compress compared to massage alone during active second stage of labour in nulliparas: A randomised trial. (March 2022) - Hong, Jesrine Gek Shan; Abdullah, Nadiah; Rajaratnam, Rajeev Kumar; Ahmad Shukri, Suriyanti; Tan, Sze Ping; Hamdan, Mukhri; Lim, Boon Kiong
Highlights: Nulliparity increases risk of perineal trauma during vaginal birth. Perineal massage increases vasodilatation, tissue elasticity and reduces pain. Warm compress reduces perineal pain at second stage by increasing blood flow. Perineal massage and warm compress do not reduce perineal injury requiring suturing. Women are likely to recommend perineal massage and warm compress to a friend. Abstract: Objective: To evaluate the effect of combined perineal massage and warm compress to the perineum (MassComp) compared to perineal massage alone during pushing in the second stage of labour in reducing perineal trauma requiring suturing in nulliparas. Study Design: A randomised trial was performed in a University hospital, Malaysia from June 2020 to May 2021. 281 term nulliparas who were about to start pushing in the second stage of labour were randomised to combined perineal massage and warm compress or perineal massage alone to the perineum. Primary outcome was suturing for perineal injury (episiotomy or tear). The Chi-square test was used to analyse categorical data, Student t test to compare means and distributions for normally distributed continuous data and Mann Whitney U test for appropriate ordinal data. Results: Data from 277 participants (140 MassComp arm, 137 perineal massage alone arm) were analysed based on modified intention to treat basis. Perineal suturing rates were 133/140(95.0%) [MassComp] vs. 128/137(93.4%) [perineal massage alone] RR 1.02(95%CI 0.96–1.08), P = 0.615. Of the secondary outcomes, Likert scale response to recommend allocated treatment to a friend was 103/140(73.6%) vs. 84/137(61.3%) RR 1.20(95%CI 1.02–1.42)NNTb 9(95%CI 4.3–76.4) P = 0.029, participants' satisfaction with care (visual numerical rating scale 0–10) median [interquartile range] 6[6–8] vs. 6[5–8] P = 0.392, intervention to delivery intervals were 25[15–35] vs. 19[14–30] minutes P = 0.012, major perineal injury (episiotomy, second degree or higher tears) rates 116/140(82.9%) vs. 119/137(86.9%) RR 0.95(95%CI 0.86–1.05), P = 0.404, episiotomy rates 97/140(69.3%) vs. 97/140(70.8%) RR 0.98(95%CI 0.84–1.14), P = 0.795, and spontaneous vaginal delivery rates 103/140(73.6%) vs. 106/137(77.4%) RR 0.95(95%CI 0.83–1.09), P = 0.488 for MassComp vs. perineal massage alone respectively. Other maternal and neonatal outcomes were not significantly different. Conclusion: Massage and warm compress during pushing did not decrease the likelihood of perineal injury requiring suturing in nulliparas when compared to perineal massage alone. Women were more likely to recommend massage and warm compress during pushing to a friend.